Perangkat Lunak Pengajuan Dana Bos Pada Kementerian Agama (Kemenag) Ogan Komering Ilir (OKI) Berbasis Web - Sakban Arifin; Jemakmun Jemakmun; Hutrianto Hutrianto (Journal of Information Technology Ampera, 2020)
The software for submitting School Operational Assistance funds is an improvement in the quality of education by providing educational funding from School Operational Assistance National Budget funds. Ministry of Religion and schools still experience difficulties in carrying out bookkeeping usage and the results of spending from School Operational Assistance funds. So that this study aims to create a web-based application that makes it easy for admins to examine all School Operational Assistance funds and input submissions & reports that have collected report data. Submission is an activity aimed at providing information about the causes and consequences of a policy that is being implemented, while School Operational Assistance is a government program which is basically to provide funding for non-personnel operational costs. In this study data collection was carried out by observation, interview, and literature methods and the development of software prototyping systems as the basis of the concept of working models with the aim of developing the model into a final system